CD14 Plays a Protective Role in Experimental Inflammatory Bowel Disease by Enhancing Intestinal Barrier Function - Buchheister, Stephanie; Buettner, Manuela; Basic, Marijana; Noack, Andreas; Breves, Gerhard; Buchen, Barbara; Keubler, Lydia M.; Becker, Christoph; Bleich, Andre (American Journal of Pathology, 2017)
Intestinal homeostasis disturbance through intestinal barrier disruption presumably plays a key role in inflammatory bowel disease (IBD) development. Genetic and candidate gene analyses in an Il10-deficient IBD mouse model system identified Cd14 as a potentially protective candidate gene. The role of Cd14 in colitis development was determined using dextran sulfate sodium (DSS)-induced acute and an Il10-deficiency-induced chronic model of intestinal inflammation. Intestinal permeability was investigated by fluorescein isothiocyanate-dextran uptake assay, quantitative RT-PCR analysis of tight junction proteins, myosin light chain kinase, and proinflammatory cytokine expression. Immunohistological staining of occludin, Ki-67, NF-κB-p65, and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling assay was performed, and intestinal inflammation severity was evaluated histologically. Untreated B6-Cd14-/- mice and wild-type controls did not differ in intestinal barrier function. However, DSS-treated Cd14-deficient and B6-Il10-/-Cd14-/- mice exhibited more severe intestinal barrier disruption, with increased histological scores and proinflammatory cytokine expression, compared to controls. Therefore, Cd14 deficiency did not influence epithelial integrity under steady-state conditions but caused intestinal barrier dysfunction under inflammation. As expected, CD14 overexpression increased barrier integrity. No difference in intestinal epithelial NF-κB translocation was observed between the investigated groups. Intestinal myosin light chain kinase expression decreased in Cd14-deficient mice under steady-state conditions and in the chronic model, whereas no difference was detected in the DSS models. Thus, CD14 plays a protective role in IBD development by enhancing intestinal barrier function.
EVALuna2:33906